THE EFFECT OF THE AGE OF SMOOTH BROME (BROMOPSIS INERMIS) STANDS ON THEIR HERBAGE YIELD IN TYUMEN PROVINCE - N. A. Feoktistova (Труды по прикладной ботанике, генетике и селекции, 2019)
Background. The primary specialization branches of agriculture in Tyumen Province are plant production and dairy farming, with cattle husbandry being lately introduced, which implies a demand for feed crops, in particular perennial grasses, among which smooth brome (Bromopsis inermis (Leyss.) Holub) is the most widespread. With such demand in mind, the Research Institute of Agriculture for the Northern Trans-Urals has been engaged in studying pasture grasses in order to find and develop new lines adaptable to local conditions. The purpose of the study was to examine the dynamics in forage productivity of smooth brome for a 4-year period of utilization to produce varietal characteristics of the breeding material.Materials and methods. Observations were carried out in 2014–2017 in a competitive testing nursery (CTN) set up for smooth brome plants sown in 2013. Cultivars and breeding lines, 17 accessions in total, were the material of the study. Their herbage yield was analyzed for 4 years when the grass stand was utilized (5 years of life). The accessions were classified into productivity groups and according to their utilization possibilities. Results and conclusions. Over the 4-year period of utilization in the CTN, the smooth brome accessions were distributed into 6 productivity groups according to the amounts of herbage collected – from 8 to 30 t/ha (with an interval of 4 t/ha). In the 1st and 2nd years of testing, the yield was in the range of 21.3–30 t/ha; in the 3rd and 4th years, there was a decrease to 8.0–19.6 t/ha. Comparison of the data for each of the accessions showed that all of them reduced their productivity to varying degrees – from 32 to 72%, the evidence of a significant difference between them. Thus, it became possible to divide them into 3 groups, reflecting their advantages in the context of targeted utilization in the environments of Tyumen Province: I. Haymaking group: accessions with the highest herbage yield in the 1st year of utilization (28–30 t/ha) and its significant decrease by 68–72% to the 4th year of utilization may be suitable for short-term use in field crop rotations (the reference ‘Langepas’; 7-1-67; 10-1-15; 19-3-37). II. Haymakinggrazing group: accessions with medium productivity in the 1st year of utilization (24–27 t/ha) and its moderate reduction by 42–64% to the 4th year of utilization can be used in forage rotations for 5–7 years (‘Argonavt’; ‘Ingair’; ‘Stepasha’; ‘Yarilo’; 7-1-54; 15-2-63; 4-4-17; 7-4-49; 4-2-20). III. Grazing group: accessions with low productivity in the 1st year of utilization (20–23 t/ha) and its slow decline by 39–50% to the 4th year of utilization are promising for long-term exploitation when pastures are established, or special-purpose lawns are sown, or disturbed lands are recultivated (‘Sverdlovsk 38’; ‘Zauralets’; 5-3-8; 1-11).